Genetic diversity of cultivated Gayo Arabica Coffee (Coffea arabica L.) based on morphological and microsatellite markers - Rita Andini; Ahmad Zaelani; Muhammad Ikhsan Sulaiman; Enny Rimita Sembiring; Rachman Jaya; Meenakshi Gusain; Deepak Bhanot; Roma Sarnaik Morghade; Abdel-Rhman Z. Gaafar; Abdul Azis; Heru Prono Widayat (BMC Plant Biology)
Abstract Background Indonesia is the fourth largest global producer of coffee (Coffea spp.). The primary production centre for Coffea arabica in the country is the Gayo Highlands of Aceh. The Gayo Highlands in Aceh serve as a key arabica coffee-producing region, covering over 100,000 hectares across three districts: Aceh Tengah, Bener Meriah, and Gayo Lues, situated at elevations ranging from 900 to 2,000 m above sea level (asl). Despite the economic significance of Gayo Arabica coffee, studies on its genetic diversity remain limited. The objective of this study was to evaluate the morphological characteristics, particularly those associated with yield, and their genetic diversity. Results We measured two types of analyses: a) morphological characteristics (N = 32 characteristics) were analysed from 51 accessions, with the resulting data categorised into qualitative and quantitative traits. The assessment of qualitative traits was conducted through visual observation, while quantitative traits were measured. The mean values of these traits were then subjected to Principal Component Analysis (PCA) in order to ascertain the principal contributing variables. In order to provide a comprehensive evaluation, genetic diversity was analysed using molecular markers in addition to the morphological assessments; b) genomic DNA was extracted from young leaf tissues [N = 52 samples; -1 robusta as outgroup was sampled], and a polymerase chain reaction (PCR) was conducted using eight microsatellite (SSR) markers. Subsequent analyses were then performed on the resulting DNA profiles, utilising clusterisation methodologies. The results indicated significant morphological variation among the accessions, yet comparatively low genetic diversity, as evidenced by a Nei's genetic diversity index of 0.36. Each SSR marker detected 2 to 4 polymorphic bands. Markers Sat227 and Sat240 produced 2 to 3 bands, while M24, Sat32, and A8847 revealed an average of 4.5 bands per marker. Sat207, Sat255, and AY2434 each produced three bands, with Sat255 classified as moderate in polymorphism based on prior literature. This finding suggests that a genetic bottleneck may have occurred in the Gayo Highlands arabica population. Conclusion This work will be of particular relevance to breeding programs and conservation initiatives aimed at ensuring the sustainability of arabica coffee cultivation in Indonesia and other tropical highland regions. We found a relative high morphological diversities in terms of phenotypic trait (N = 32 traits) esp. in these yield related-traits e.g. leaf number per axil, number of leaves per branch, number of cherries per branch, etc.. However, the genetic diversity measured in this study by employing 51 arabica coffee accessions was found to be relatively low, namely 0.34. Furthermore, the use of Principal Component Analysis (PCA) helped to distil complex trait data, with the first principal component (PC1) accounting for 35.6% of the total variation, mainly driven by leaf- and yield-related characteristics. The findings of this study on the present genetic diversity of C. arabica will doubtless underpin future endeavours to enhance the species genetically, to develop future breeding programmes, and to improve the quality of the various varieties.